PENGARUH PELATIHAN DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR SEBAGAI VARIABEL INTERVENING PADA BIRO UMUM DAN PENGADAAN KEMENTERIAN PERTANIAN RI - Natasya Rizkya (2022)
This study used a quantitative approach that aim to find out and prove the influence between training and career development on the employee performance of the Bureau of General Affairs Management and Procurement of the Ministry of Agriculture of the Republic of Indonesia with organizational citizenship behavior as an intervening variable. This study used 70 respondents, with non-probability sampling techniques using Incidental Sampling. The analysis used, namely validity test, reliability test, determination coefficient test (R2), track coefficient test, t-test and F test using SmartPLS 3.0. The results showed that: (1) Partially, training has a positive and significant influence on employee performance. (2) Partially, career development does not have a positive and significant influence on employee performance. (3) Partially, training does not have a positive and insignificant influence on employee performance through Organizational Citizenship Behavior. (4) Partially, career development does not have a positive and insignificant influence on employee performance through Organizational Citizenship Behavior. (5) Simultaneously, training and career development affect employee performance through Organizational Citizenship Behavior as an Intervening variable.